QUALITATIVE AND QUANTITATIVE ANALYSIS OF MICRO AND MACRO ASPECTS OF AGRICULTURAL FINANCE - Veselinović, Branislav; Drobnjaković, Maja (Economics of Agriculture, 2014)
The epicenter of this analysis is to provide an overview of the current situation in micro and macro agricultural fnance in Serbia and the EU. One of the goals of this research is to consider the weaknesses and potentials of agricultural policy in Serbia, through comparison with more developed countries. In this qualitative and quantitative analysis, authors used comparation method, analysis and synthesis method, inductive and deductive method, and a local and international literature review. There are several important conclusions which can be drawn from this manuscript. Access to fnance among farmers and agricultural SMEs is among the poorest of any sector in Serbia. The Serbian fnancial sector offers a poor range of loan products to the agricultural sector. Therefore, existing mechanisms for micro and macro agricultural fnance in Serbia are not adequate and a change should be made in approach.